Challenges in Accessing Higher Education: A Semiotic Analysis on Gender Stereotypes, Cultural Conservatism, and Economics - Kurniawan, Kurniawan; Arnas, Riska; Salida, Amrizal; Fadlina, Fadlina; Hamdi, Hamdi; Maryam, Maryam (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study investigates the role of logo symbolism in shaping the identity and communication strategies of State Islamic Universities (UINs) in Central Java, Indonesia. Logos serve as powerful visual representations of an institution's identity, blending cultural and religious values. Despite their importance, there is limited research on the semiotic analysis of UIN logos, particularly in terms of integrating Islamic identity with local cultural heritage. This research examines the challenges faced by the Towani Tolotang community in Indonesia, focusing on gender stereotypes, cultural conservatism, and economic barriers to higher education, especially for women. The Towani Tolotang community’s adherence to traditional values often creates a conflict between higher education and cultural preservation, limiting educational opportunities. Gender expectations and economic limitations further exacerbate this issue, with women’s education often deprioritized and financial constraints hindering access to higher education. This study adopts a qualitative descriptive approach, utilizing semiotic analysis based on Charles Peirce's theory and Cerrato’s color theory. Data was gathered through documentation techniques from online repositories, focusing on logos from five UINs in Central Java. Findings indicate that these logos incorporate Islamic values while reflecting local cultural heritage, using symbols such as gunungan, flowers, and specific color schemes (green, white, yellow, orange, gold, and black). These logos not only embody cultural preservation but also promote progressive Islamic education. The study underscores the significance of logo symbolism in reinforcing institutional identity, enhancing public perception, and boosting the competitiveness of UINs globally.